Effect of cardiac rehabilitation on the nociceptive threshold increased of hypertensive subjects. - Desiderio Maldonado, Ana Clara; Prado, João Paulo; Nema de Aquino, Tarcísio; de Carvalho Vidigal, Fernanda; Bassalobre Carvalho Borges, Juliana; Galdino de Souza, Giovane (Fisioterapia Brasil, 2022)
Objectives: Hypertensive subjects have an increased nociceptive threshold, which may contribute to the pain perception reduction. Thus, the aim of this study was to evaluate the effect of a cardiac rehabilitation program (CRP) on the increased nociceptive threshold of hypertensive subjects. Methods: Forty-one participants were divided into two groups: a normotensive group and hypertensive group. In both groups, the body mass index, abdominal circumference, systolic and diastolic blood pressure, heart rate, nociceptive threshold and functional capacity by six-minute walking test (6MWT) were evaluated. The CRP was composed of aerobic exercises on a treadmill for 30 min, 3 times a week for 7 weeks. Results: After the CRP, there was a reduction (p < 0.001) in the mechanical nociceptive threshold and an increase in the distance walked during the 6MWT (p < 0.001) in the hypertensive group. No differences were found in the body mass index between the groups. Conclusion: The results of the present study suggested that aerobic exercise is an important modality to normalize the nociceptive threshold and improved the functional capacity of the hypertensive subjects.